2019
DOI: 10.1186/s13046-019-1459-6
|View full text |Cite
|
Sign up to set email alerts
|

GSTZ1 deficiency promotes hepatocellular carcinoma proliferation via activation of the KEAP1/NRF2 pathway

Abstract: BackgroundGlutathione S-transferase zeta 1 (GSTZ1) is the penultimate enzyme in phenylalanine/tyrosine catabolism. GSTZ1 is dysregulated in cancers; however, its role in tumorigenesis and progression of hepatocellular carcinoma (HCC) is largely unknown. We aimed to assess the role of GSTZ1 in HCC and to reveal the underlying mechanisms, which may contribute to finding a potential therapeutic strategy against HCC.MethodsWe first analyzed GSTZ1 expression levels in paired human HCC and adjacent normal tissue spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 46 publications
2
39
1
Order By: Relevance
“…[63] GSTZ1 expression is downregulated in tumor tissue compared to adjacent normal tissue and correlates with poor prognosis. [250] High GSTP1 expression correlates with better survival and smaller tumor size. [254] Lung cancer GPX3 expression is decreased in NSCLC tissues.…”
Section: Tumor Type Involvement Of the Gsh Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…[63] GSTZ1 expression is downregulated in tumor tissue compared to adjacent normal tissue and correlates with poor prognosis. [250] High GSTP1 expression correlates with better survival and smaller tumor size. [254] Lung cancer GPX3 expression is decreased in NSCLC tissues.…”
Section: Tumor Type Involvement Of the Gsh Systemmentioning
confidence: 99%
“…In that regard, GPX1, GPX3, and GPX7 expression were found to be decreased [ 144 , 240 , 241 , 242 , 243 ] in tumor tissues, while the expression of GPX2 and GPX4 was found to be upregulated [ 144 , 146 , 244 , 245 , 246 , 247 ]. In addition, GSTA1, GSTM1, and GSTZ1 are reported to be downregulated in tumor tissue and can correlate with a poor prognosis [ 63 , 248 , 249 , 250 , 251 ], while GSTT1, GSTO1, and GSTK1 are mostly reported to be upregulated in tumor tissue compared to the normal surrounding tissue [ 252 , 253 ]. The expression level of GSTP1 in tumor tissue is controversial [ 144 , 253 , 254 , 255 ], and its involvement in tumorigenesis could at least in part depend on its hypermethylation [ 256 , 257 , 258 , 259 , 260 ].…”
Section: Redox Homeostasismentioning
confidence: 99%
“…It participates in the catabolism of phenylalanine/tyrosine and catalyzes the isomerization of maleylacetoacetate to fumarylacetoacetate 18 . We previously found that GSTZ1 was poorly expressed in HCC, and GSTZ1 deficiency could lead to metabolite succinylacetone accumulation and thereby activate the nuclear factor erythroid 2-related factor 2 (NRF2) signaling pathway 19 , 20 . Considering the importance of GSTZ1 in the development and progression of HCC, GSTZ1 may be an anticancer hallmark for sorafenib resistance in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Second, GSTZ1 (-/-) knockout mice demonstrated upregulation of NQO1 and activation of Nrf2-mediated antioxidant response pathways (Blackburn et al, 2006). Third, GSTZ1 knockout in hepatoma cells decreased glutathione concentrations, resulting in activation of Keap1/Nrf2 (Li et al, 2019). These studies show oxidative stress responses are activated following genetic ablation of GSTZ1.…”
Section: Discussionmentioning
confidence: 74%